Network attacks and exploitation : a framework - Monte, Matthew (Indianapolis, IN : Wiley, 2015)
This book provides a roadmap for developing a complete offensive and defensive strategy to engage in or thwart hacking and computer espionage. It helps you understand the principles of the space and look beyond the individual technologies of the moment to develop durable comprehensive solutions. Numerous real-world examples illustrate the offensive and defensive concepts at work, including Conficker, Stuxnet, the Target compromise, and more. You will find clear guidance toward strategy, tools, and implementation, with practical advice on blocking systematic computer espionage and the theft of information from governments, companies, and individuals. --
Computer Network Exploitation -- The Attacker -- The Defender -- Asymmetries -- Attacker Frictions -- Defender Frictions -- Offensive Strategy -- Defensive Strategy -- Offensive Case Studies.
Includes bibliographical references and index.
Online resource; title from PDF title page (EBSCO, viewed July 15, 2015).
Keywords: Business enterprises -- Computer networks -- Security measures; Computer security; Computer crimes -- Prevention; Corporations -- Security measures; BUSINESS & ECONOMICS / Industrial Management; BUSINESS & ECONOMICS / Management; BUSINESS & ECONOMICS / Management Science; BUSINESS & ECONOMICS / Organizational Behavior; Business enterprises -- Computer networks -- Security measures; Computer crimes -- Prevention; Computer security; Corporations -- Security measures; Electronic books; Electronic books